A Comparison of the International Charters on Geographical Education. Issue 4 (4th July 2018) - Bourke, Theresa; Lane, Rod
Abstract: This article uses discourse analysis techniques associated with Foucauldian archaeology to examine the two international charters developed by the International Geographical Union Commission on Geographical Education (IGU-CGE), the original one in 1992 and the revised version endorsed in 2016 at the Beijing conference. The examination considers the consultation and development processes before outlining similarities and differences in the messages communicated and how discourses have changed through time. The article concludes with recommendations for the geography education community for the future.